PERLINDUNGAN HAK ULAYAT MASYARAKAT ADAT DALAM HUKUM POSITIF DI INDONESIA - Danel Aditian Situngkir (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
According to Bagir Manan, the provisions of article 33 paragraph 3 of the 1945 Constitution are constitutional rights of the state's right to control over the land, water and natural resources contained therein. The right to control the State based on the constitution is used for the greatest prosperity of the people. The two rules cannot be separated from one another, both are a systematic unit. Legal protection for indigenous peoples is regulated in Law Number 18 of 2004 concerning Plantations (Plantation Law). Article 9 paragraph (2) of the Agriculture Law confirms that if the application for the right to a plantation business is on ulayat land which in reality still exists, the applicant for the right is obliged to hold deliberations with the indigenous people concerned to obtain an agreement regarding the surrender of the land and compensation (compensation). In the mining sector, there is a need for government oversight, in supervising the management of mines in their territory, including the role of the local government so that mining operations comply with predetermined provisions and ensure the safety of the surrounding community, including indigenous peoples. In the provisions of Article 139 paragraph (1) of the Mining Law that the Minister provides guidance on the implementation of mining business management carried out by the provincial government and regency/city government in accordance with their authority.Keywords: Protection, Community Rights, Customs, HR Management, West Sumatra.